Implications of Standard Clauses in Law No. 8 of 1999 on Consumer Protection for Businesses and Consumers - Siregar, Hisar; Situmorang, Samuel; Pasaribu, Fransisko (Golden Ratio of Data in Summary, 2025)
Law No.8 Standard clauses, as part of standard contracts often used in business transactions, have significant implications for both parties, namely businesses and consumers.This study aims to analyze how standard clauses in the law affect consumer protection and business liability.Through a qualitative analysis method, it is found that standard clauses often benefit businesses but can harm consumers if not properly regulated.Therefore, effective law enforcement and consumer education are needed to address this imbalance and ensure fairness in transactions.